The Factors Influencing Feeding Practices of Primary Caregivers of Preschoolers: A Theory-Based Cross-Sectional Study - Qutaibah Oudat; Rebecca C. Lee; Elaine L. Miller; Sarah Collins Couch; Tamilyn Bakas (Children)
Background/Objectives: Primary caregivers play a pivotal role in shaping children’s dietary behaviors, which are critical in preventing childhood obesity. This study aimed to examine the extent to which demographic characteristics and caregiver factors, including dietary beliefs and intentions to provide a healthy diet, influence feeding practices among primary caregivers of preschool-aged children. Methods: This study included a cross-sectional dataset comprising data collected from 146 primary caregivers of preschool-aged children (3–5 years). Participants were recruited using snowball and convenience sampling from Facebook and community settings in Cincinnati, Ohio. Feeding practices were assessed using the Comprehensive Feeding Practices Questionnaire (CFPQ), while caregiver demographic characteristics, dietary beliefs, and intentions were measured through self-administered surveys. Hierarchical multiple linear regression was employed to identify predictors of feeding practices. Results: The findings reveal that primary caregivers’ feeding practices were shaped by multiple factors, including dietary beliefs (behavioral, normative, and control), intentions, and demographic characteristics. Each subscale of feeding practices was predicted by different factors, highlighting the unique influence of these factors on feeding behaviors. Conclusions: This study underscores the complex interplay between caregiver cognitive (dietary beliefs and intentions) and demographic factors in shaping feeding practices. The findings highlight the importance of targeting caregiver beliefs and intentions in interventions aimed at promoting healthier feeding practices, contributing to the prevention of childhood obesity. Importantly, future research is needed to explore these factors in more diverse populations and validate cognitive measures for broader application.